A Structural Equation Model on Occupational Stress Among Police Officers - H. Falloran, Love; L. Genuba, Rinante; A. Lovina Jr, Rogelio (International Journal of English Literature and Social Sciences (IJELS), 2022)
The aim of this research is to construct a causal model on occupational stress through the perception of barriers, work environment, and frustration discomfort of police officers. This study was also set up to provide a research-based landscape of the occupational stress among police officers viewed in the local Police Station of Misamis Occidental, Region X, Philippines. Survey and correlational methods of research and structural equation model were used in the study involving 400 police officers. Findings revealed that the level of occupational stress, work environment, and frustration discomfort was high and moderate for the perception of barriers. Results also show that there was a positive correlation between barrier perception and workplace stress, work environment and work stress, frustration discomfort, and work stress. Moreover, perception of barriers, work environment, and frustration discomfort are predictors of occupational stress. In addition, to express the latent variable frustration discomfort representing the measured variables entitlement, emotional intolerance, achievement, and discomfort intolerance, as the best fit model for occupational stress among police officers.